The Significance Of The Computer Simulation Method In Medical Education - Yusupova Rana Irkinovna; Abdullaeva Sabakhon Azatovna (Zien Journals, 2024)
Today's task of education is to teach students to be able to work independently in the informationeducational conditions that are improving day by day, to use the flow of information wisely. Comprehensive reforms in the structure of the educational system will be strengthened by teachers by mastering advanced pedagogical technologies and using them in the educational process. For this, pedagogues are required to learn and apply the technological approach to the educational process. With the wide development of advanced technologies, in recent years, new pedagogical clinical work-game technologies have been effectively used to optimize education in medical universities.
Keywords: Pedagogical technologies; simulation education; new pedagogical technology